Significance of Geomorphic Factors on Land Use Palnning and Development in Bikaner - Sen, Amal Kumar; Singh, Surendra (Annals of Arid Zone, 2016)
Geomorphic and land use surveys of the Bikaner district of Western Rajasthan have been conducted as a part of a comprehensive survey carried out by the Basic Resources Survey Division of the Central Arid Zone Research Institute. By a faithful correlation of the land use and geomorphic maps, arising out of our field surveys, the variations of land use in different geomorphic units are worked out. The relationship between the geomorphology and the land use in the area is then examined. It shows that a relation exists between the two. The macro and micro geomorphic factors affecting the intensity of cultivation are studied in this context. In this area, wind erosion and slopes have been found to be the important factors which influence the distribution of cultivated lands and the intensity of their use. The data obtained in the course of field surveys are statistically analysed in order to find out the significance of micro geomorphic factors controlling cultivation in the areas of significance of geomorphic differences. The study reveals that the effect of erosion is more pronounced and significant than other factors. As such, it is suggested that any programme adopted for land use planning should be in the direction of wind erosion control, aided or correlated with modern dry farming or irrigation farming techniques.